Pengaruh Sosial Ekonomi terhadap Minat Pemuda dalam Melakukan Wirausaha Tanaman Hias di Desa Sidomulyo Kecamatan Batu Kota Batu - Setyawati , Yuni ; Setyowinahyu K.B , Citra (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
This research aims to determine a description of socio-economic factors as well as youth interest in the ornamental plant entrepreneurship in Desa Sidomulyo, Kecamatan Batu, Kota Batu. socio-economic influence on youth interest in entrepreneurship of ornamental plants in Desa Sidomulyo, Kecamatan Batu, Kota Batu. Socio-economic factors that have the most dominant influence on youth interest in entrepreneurship of ornamental plants in Desa Sidomulyo , Kecamatan Batu Kota Batu . Data were collected through questionnaires, interviews and documentation. The data were tested its validity and reliability . Samples were 50 respondents with sampling technique using purposive sampling. This research used statistical analysis techniques in the form of multiple linear regression to test the effect of income, family environment, community environment and social status of entrepreneur interest either partially or simultaneously. The results of the research were characteristic of respondent's data, income level, family environment, community environment, social status and youth entrepreneur interest. Based on multiple linear regression test indicated that income, family environment, social environment and social status have positive and significant influence to youth entrepreneur interest either partially or simultaneously. From several socioeconomic factors studied, income factor have dominant influence to interest of youth to entrepreneurship of ornamental plant in Desa Sidomulyo Kecamatan Batu.